High Prevalence of Drug–Drug Interactions in Primary Health Care is Caused by Prescriptions from other Healthcare Units. Issue 5 (13th December 2017) - Andersson, Marine L.; Böttiger, Ylva; Kockum, Henrik; Eiermann, Birgit
Abstract: Drug–drug interactions are increasingly common, as patients are getting older and the number of drugs per patient is increasing. In this study, we investigated to which extent potential drug–drug interactions originated from single or multiple prescribers. All patients attending any of 20 primary healthcare centres were included in a retrospective observational cohort study. Data on all prescriptions to these patients, irrespectively of the prescriber, were collected for two 4‐month periods. Potential drug interactions were identified using the drug–drug interaction database SFINX. Interactions were classified with respect to the workplace of the prescriber, and the prevalence of interactions according to origin was analysed. We found that the drug interactions were significantly more common when the drugs were prescribed from different healthcare centres, compared with drugs prescribed from the patients' primary healthcare centre only. One explanation for this increased risk of drug interactions could be that the prescribers at different primary healthcare centres do not share the same information concerning the total medication list of the patient.